PEMERIKSAAN KADAR ALANIN AMINOTRANSFERASE (ALT) TERHADAP LAMA PAPARAN KARBON MONOKSIDA PADA PEKERJA BENGKEL DI JEMUR WONOSARI SURABAYA - Ersalina Nidianti; Desi Susanti; Siti Basiroh; Adinda Priyanti Dewi (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Carbon monoxide is one of the most important pollutants and has toxic properties if the gas is inhaled by humans. Levels of alanine aminotransferase (ALT) and ALT enzymes become one of the biomarkers that affect liver damage. The ALT enzyme is a transferase enzyme that is released when the liver is damaged. The purpose of this study was to determine the effect of long exposure to carbon monoxide (CO) on workshop workers on the examination of ALT levels. The research method used is an experimental method with a one-shot case study design on 27 respondents of workshop workers in the Jemur Wonosari area of ​​Surabaya. ALT levels were measured using a photometer and analysis of ALT levels was carried out using the One-way ANOVA statistical test using SPSS. The results showed the average ALT levels in group X1 (long working 1-5 years) of 38.26 u/l while the average result in group X2 (long working 6-10 years) was 40.38 u/l and average results in group X3 (long working 11-15 years old) is 41.11 u/l. One way ANOVA statistical test obtained a significance value of 0.484> 0.05. So the conclusion obtained in this study is that there is no effect of long exposure to carbon monoxide on the examination of ALT levels in the blood of workshop workers in Jemur Wonosari Surabaya.